STEM-орієнтовані ігрові технології у підготовці студентів до викладання математики в початковій школі - Бевзюк Марина; Bevziuk Maryna; Білан Валентина; Bilan Valentyna (Видавництво «Код», 2025)
Резюме. У статті розглядається проблема впровадження STEM-орієнтованих ігрових технологій у процес професійної підготовки майбутніх учителів початкової школи, зокрема у викладанні математичної освітньої галузі. Актуальність дослідження зумовлена необхідністю оновлення змісту педагогічної освіти відповідно до сучасних тенденцій розвитку науки, техніки, технологій та суспільства.

Abstract. The article discusses the problem of introducing STEM-oriented gaming technologies into the process of professional training of future primary school teachers, in particular in teaching mathematics. The relevance of the study is determined by the need to update the content of teacher education in line with current trends in science, technology, and society. In the context of the digitalization of education and the spread of innovative approaches to learning, the STEM approach, which integrates knowledge from the natural sciences, technology, engineering, and mathematics, is of particular importance, promoting the formation of interdisciplinary thinking, the ability to conduct systematic analysis, research activities, and creative solutions to professional tasks in students. The study emphasizes that gaming technologies are an effective tool for implementing STEM education in teacher training, as they ensure active interaction between students and educational material, increase their cognitive motivation, and contribute to the formation of key professional competencies. The author clarifies the classification of STEM-oriented games in teacher training, which is divided into three main groups: didactic games aimed at mastering basic mathematical concepts and patterns; simulation games that model real pedagogical situations and allow students to master analysis and decision-making skills; project-research games that involve the creation of educational models, conducting experiments, developing educational cases or STEM projects. It is noted that mastering STEM-oriented gaming technologies during training at a pedagogical institution contributes to the simultaneous development of students’ professional, methodological, and social and communication competencies. Professional subject competence is formed through the acquisition of in-depth mathematical knowledge and skills for its practical application in the school mathematics course; methodological competence is formed through the ability to design the educational process, select gaming tools in accordance with the age characteristics of students and the goals of STEM education; social and communication competence is formed through teamwork, the development of leadership qualities, empathy, and communicative flexibility. STEM-oriented game technologies ensure the comprehensive integration of the cognitive, emotional, and activity spheres of the future teacher’s personality, form an interest in pedagogical innovations, develop analytical thinking, creativity, and readiness to use innovative approaches in professional activities. The article substantiates that the systematic introduction of STEM-oriented games into the training process of students majoring in Primary Education contributes to improving the quality of mathematical training, stimulates cognitive activity, and prepares teachers to work in the conditions of the New Ukrainian School.
STEM-oriented gamification technologies in preparing students to teach mathematics in primary school
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: STEM-освіта; ігрові технології; підготовка майбутніх учителів; математична освітня галузь; початкова школа; професійна компетентність